Consumer perception towards private label brands in the Republic of Serbia - Macura, Nikola; Petrov, Viktorija; Nuševa, Daniela; Vukmirović, Goran; Vučenović, Sonja (Industrija, 2025)
Private label brands have an important role in modern economy-oriented consumption. Private label brands have large market shares in developed countries with market share rates that often exceed 50% of the total market share. This means that every second or at least every third purchased product is some kind of private label brand. The market of the Republic of Serbia is also moving in this direction, with increasing consumer awareness of the benefits that these brands provide to them. The importance that private label brands have for the identity of trade companies and their positions on the market has become irreplaceable. As part of the work, the results of a survey conducted on respondents in two cities in the Republic of Serbia were analyzed in order to examine their perceptions of private label brands. The research results were analysed by the factor analysis as a statistical technique for data reduction. Also, non-parametric tests are done in order to determine statistical significance of diferences between different sample groups regarding to private label brands in Serbia. The aim of the paper is to clarify the concept of private label in modern trade, to point out some prejudices about products under these brands and to additionally clarify consumer perceptions of private label brands.
Keywords: Private Label, Factor Analysis, Trade, Republic of Serbia, Market